Effect of a Synthetized Herbal Remineralizing Paste on Enamel Microhardness - Shokripour, Mohadese; Kavousinejad, Shiva (Journal of Dental School, 2024)
Objectives This study aimed to synthesize an herbal remineralizing paste containing the extracts of Miswak, licorice, aloe vera, propolis, and honey and compare its effect with 5% sodium fluoride (NaF) and 1.23% acidulated phosphate fluoride (APF) on demineralized enamel microhardness. Methods This experimental study was conducted on 72 extracted sound premolars. After obtaining the extracts and synthesis of the herbal paste, the baseline microhardness was measured, and the samples underwent a 14-day pH cycling. Next, the teeth were randomly assigned to six groups (N=12) for application of (I) 5% NaF for one minute, (II) 1.23% APF for one minute, (III) herbal paste for one minute, (IV) herbal paste for five minutes, (V) herbal paste for 15 minutes, and (VI) herbal paste for six hours. The microhardness was measured again. Data were analyzed by one-way analysis of variance (ANOVA) (alpha=0.05). Results The mean final microhardness was significantly higher than the primary microhardness in all groups (P<0.05). The highest microhardness was noted in group IV, followed by II, VI, I, V and III. One-way ANOVA revealed no significant difference between the final microhardness of study groups (P=0.97). Conclusion The effect of synthesized herbal paste on demineralized enamel microhardness was comparable to that of 5% NaF and 1.23% APF. Due to the lack of a significant difference in duration of application, this paste may be applied for one minute to benefit from its remineralizing effects.